A pilot study: a combined therapy using polymyxin-B hemoperfusion and extracorporeal membrane oxygenation for acute exacerbation of interstitial pneumonia - Itai, Junji; Ohshimo, Shinichiro; Kida, Yoshiko; Ota, Kohei; Iwasaki, Yasumasa; Hirohashi, Nobuyuki; Bonella, Francesco; Guzman, Josune; Costabel, Ulrich; Kohno, Nobuoki; Tanigawa, Koichi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Direct hemoperfusion with polymyxin B-immobilized fiber (PMX-DHP) might be beneficial for treating acute exacerbation (AE) of interstitial pneumonia (IP). Venovenous extracorporeal membranous oxygenation (VV-ECMO) is an emerging tool to avoid ventilator-induced lung injury. This is a report presenting the first three patients with AE of IP treated with a combined therapy of PMX-DHP and VV-ECMO. Case presentation: Patient 1 was a 68-year-old male with acute interstitial pneumonia, patient 2 a 67-year-old male with AE of idiopathic pulmonary fibrosis, and patient 3 a 61-year-old female with AE of collagen vascular disease-associated interstitial pneumonia. All patients were severely hypoxemic and required mechanical ventilation. A combined therapy using PMX-DHP and VV-ECMO was initiated with support of intravenous corticosteroids and antibiotics. Radiological findings, oxygenation and laboratory findings markedly improved and all patients survived without severe complications. Conclusion: A combined therapy of PMX-DHP and VV-ECMO might be a therapeutic option for AE of IP.